The Directed Questioning Activity for Subject Matter Text - Ryder, Randall James (Journal of reading, 1991)
The directed questioning activity (DQA) is a questioning strategy that provides scaffolded instruction to enhance students' higher-level comprehension skills. Designed to be used with expository text, the DQA promotes text comprehension through the use of advance cognitive organizers & question placement strategies. Through the presentation of directed questions & teachers' modeling of metacognitive strategies, students begin to acquire a process for self-regulation of expository text. Through the presentation of questions that seek to clarify, confirm, or infer meaning from the linking of prior knowledge to information presented in the text, students begin to acquire a process for higher-level thinking skills. 3 Figures, 20 References. AA